2020
DOI: 10.1021/acsabm.0c00240
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Dependent Bioactivity and Self-Assembling Properties of RGD-Containing Amphiphilic Peptides as Extracellular Scaffolds

Abstract: Cell adhesion is a fundamental biological process involved in a wide range of cellular and biological activity. Integrin−ligand binding is largely responsible for cell adhesion with an extracellular matrix, and the RGD sequence is an epitope in ligand proteins such as fibronectin. The extracellular matrix consists of fibrous proteins with embedded ligands for integrins. Such a biological architecture has been reconstructed for biochemical, pharmaceutical, and biomaterial studies using artificial supramolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In this manner, it was possible to tailor the differentiation of human mesenchymal stem cells, with adipogenesis being favored by softer gels with lower concentrations of RGD. In another recent work, RGD-modified hydrogels were obtained by simply changing an alanine with glycine in different positions of the well-known gelator peptide RADA16 [59]. This study showed that the substitution position has a great impact on the gelation ability and properties of the system, as well as on the cell adhesiveness.…”
Section: Rgdmentioning
confidence: 87%
“…In this manner, it was possible to tailor the differentiation of human mesenchymal stem cells, with adipogenesis being favored by softer gels with lower concentrations of RGD. In another recent work, RGD-modified hydrogels were obtained by simply changing an alanine with glycine in different positions of the well-known gelator peptide RADA16 [59]. This study showed that the substitution position has a great impact on the gelation ability and properties of the system, as well as on the cell adhesiveness.…”
Section: Rgdmentioning
confidence: 87%
“…In many cases, peptide fibers become cell adhesive if an RGD sequence is introduced to the peptide sequence exposed to aqueous media. For example, the cell adhesive peptide amphiphile [ 21 ], Fmoc–FF-based peptide fibers [ 39 ], peptide fibers with RADA repeat [ 57 ], and peptide fibers with β -heparin structure [ 66 ] have been prepared by the introduction of an RGD sequence. However, the position of introducing the RGD sequence can affect cell adhesivity.…”
Section: Applicationsmentioning
confidence: 99%
“…However, the position of introducing the RGD sequence can affect cell adhesivity. When the RGD sequence is introduced to peptide fibers having a RADARADARADARADA sequence as a self-assembly unit by replacing RAD with RGD, peptide fibers containing the RGDARADARADARADA sequence show weaker cell adhesivity compared to peptide fibers containing the RADARADARADARGDA sequence [ 57 ]. As the rigidity of peptide fibers and rearrangement of monomer peptide units influence the viability and differentiation of cells cultured on the peptide fibers, the dynamic nature of peptide fibers has been investigated in detail.…”
Section: Applicationsmentioning
confidence: 99%
“…Peptide-based self-assemblies in aqueous media are an attractive platform capable of imparting various bioactive functions by controlling the amino acid sequence. Indeed, a lot of biomaterials with superb functions have been realized by using selfassembling peptides [10][11][12][13][14][15][16][17][18][19][20]. In this work, to study self-assembly of peptides at a bilayer membrane, we designed an amphiphilic molecule Lipid-(RADA)2.…”
Section: Introductionmentioning
confidence: 99%
“…(RADA)2 peptide has alternating hydrophilic (R and D) and hydrophobic (A) amino acid residues [21]. Such an alternating sequence between hydrophilic and hydrophobic amino acid residues is known to be favorable to form a β-sheet self-assembly [18][19][20]. The alkyl chains with a fluorescent group were attached to (RADA)2 peptide as an anchoring unit into the phospholipid membranes and for direct observation under a fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%